The Effect of Inflation and the Open Unemployment Rate on the Number of Poor People In North Sumatra - Dwi Susanti (Insan Zenius Ilmiah, 2026)
This study aims to analyze the effect of inflation and the open unemployment rate on the number of poor people in North Sumatra Province during the period 2007–2020. The focus of this study is to determine the extent to which macroeconomic factors such as inflation and unemployment affect poverty levels in areas with diverse economic structures between urban and rural areas. This study uses a quantitative approach with secondary data obtained from the Central Statistics Agency (BPS). The analytical method used is multiple linear regression with the Ordinary Least Square (OLS) approach, and is complemented by classical assumption tests such as normality, autocorrelation, multicollinearity, and heteroscedasticity tests to ensure the model used meets the BLUE (Best Linear Unbiased Estimator) criteria. The results of the study indicate that partially, the unemployment variable has a positive and significant effect on poverty with a probability value of 0.0006 <0.05, which means that every 1 percent increase in unemployment increases the number of poor people by 0.0419 percent. Meanwhile, inflation also has a positive and significant effect on poverty with a probability value of 0.0305 < 0.05, where every 1 percent increase in inflation increases the number of poor people by 0.0722 percent. Simultaneously, inflation and unemployment have a significant effect on poverty with an R-Squared value of 0.6684. This finding emphasizes the importance of inflation control policies and job creation as strategic efforts to reduce poverty levels in North Sumatra Province.